2010
DOI: 10.2353/ajpath.2010.090914
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Cytokines Are Involved in the Initiation of the Abnormal Matrix Process in Pseudoexfoliation Syndrome/Glaucoma

Abstract: Pseudoexfoliation (PEX) syndrome, which is an age-related, generalized elastotic matrix process, currently represents the most common identifiable risk factor for open-angle glaucoma. Dysregulated expression of proinflammatory cytokines has been implicated in the initiation of various fibrotic disorders and in the pathophysiology of glaucoma. Here we investigated the presence, expression, regulation, and functional significance of proinflammatory cytokines in eyes with early and late stages of PEX syndrome/gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 39 publications
4
107
0
9
Order By: Relevance
“…11 Proinflammatory cytokines in eyes with early and late stages of PEX syndrome/glaucoma were studied. 12 The authors support a role for a stressinduced, spatially, and temporally restricted subclinical inflammation in the onset of the fibrotic matrix process characteristic of PEXS/PEXG. 12 Sorkhabi et al studied high-sensitivity C-reactive protein and tumor necrosis factor alpha in PEXS and mentioned that increased levels of these markers, as signs of inflammation and peripheral endothelial dysfunction, may be risk factors for systemic and ocular manifestations of PEXS.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…11 Proinflammatory cytokines in eyes with early and late stages of PEX syndrome/glaucoma were studied. 12 The authors support a role for a stressinduced, spatially, and temporally restricted subclinical inflammation in the onset of the fibrotic matrix process characteristic of PEXS/PEXG. 12 Sorkhabi et al studied high-sensitivity C-reactive protein and tumor necrosis factor alpha in PEXS and mentioned that increased levels of these markers, as signs of inflammation and peripheral endothelial dysfunction, may be risk factors for systemic and ocular manifestations of PEXS.…”
Section: Discussionmentioning
confidence: 95%
“…12 The authors support a role for a stressinduced, spatially, and temporally restricted subclinical inflammation in the onset of the fibrotic matrix process characteristic of PEXS/PEXG. 12 Sorkhabi et al studied high-sensitivity C-reactive protein and tumor necrosis factor alpha in PEXS and mentioned that increased levels of these markers, as signs of inflammation and peripheral endothelial dysfunction, may be risk factors for systemic and ocular manifestations of PEXS. 13 In contrast, high-sensitivity C-reactive protein had not been found as a predictive marker of inflammation and peripheral endothelial dysfunction in PEXS and PEXG.…”
Section: Discussionmentioning
confidence: 95%
“…The findings suggested that an increased expression of IL-6 and IL-8, which may be induced by chronic stress conditions, such as oxidative stress and hypoxia, may act as a triggering factor for the abnormal PEX material production in the early stages. 14 It is accepted that oxidative stress contributes to atherosclerosis and also to kidney injury. Antioxidant mechanisms are inefficient in chronically hemodialyzed patients, which result in increased formation of reactive oxygen species and other free radicals and consequently in oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoeksfolijacije su sistemski metabolički poremećaj vezivnog tkiva, verovatno nastao kao rezultat poremećaja sinteze i rasporeda mikrofibrila (23). Dugo se smatralo da je u pitanju poremećaj metabolizma bazalne membrane.…”
Section: Diskusijaunclassified